A representação do Capitão América no quadro político norte americano (1941-1974). - Araujo, Anderson da Silva (2020)
When we are faced with the image of the Capitain America, character of the Marvel Comics, we are led to envision him as a hero full of courage, bearer of a great patriotic spirit who wears, literally, the flag of the United States of America. Created by Joe Simon (1913-2011), and Jack Kirby (1917-1994) at the beginning of the 1940s, he has become an representative icon of the American History in comic books. The aim of our dissertation is to do an analysis of the corpus constituted by stories of the Capitain America in the period from 1941 to 1978, through which we can verify a development of the narrative in the super-hero genre, which is a very emblematic product of the American society, as well observe the character of socio-cultural identity and political ideology present in the stories of the Sentinel of Freedom, analysing central aspects of their discourse over the years. In the first phase, from 1941 to 1954, the profile of the hero was a representation of the American State itself; in the second phase, from 1964 to 1974, under the influence of the post-war tensions, the stories of the Capitain America were cancelled and the character remained ostracized until he resurfaced in the 1960s, a period of political and social crisis which made him adapt himself to the new times in order to keep on existing. Finally in 1974, in the Nomad phase, there is a change in the attitude of the character caused by frustration dued to the Watergate scandal, leading the Capitain America to break relations with the American State and become Nomad, the man without a country.